Microbial communities in petroleum-contaminated sites: Structure and metabolisms. (January 2022) - Cabral, Lucélia; Giovanella, Patricia; Pellizzer, Elisa Pais; Teramoto, Elias Hideo; Kiang, Chang Hung; Sette, Lara Durães
Abstract: Over recent decades, hydrocarbon concentrations have been augmented in soil and water, mainly derived from accidents or operations that input crude oil and petroleum into the environment. Different techniques for remediation have been proposed and used to mitigate oil contamination. Among the available environmental recovery approaches, bioremediation stands out since these hydrocarbon compounds can be used as growth substrates for microorganisms. In turn, microorganisms can play an important role with significant contributions to the stabilization of impacted areas. In this review, we present the current knowledge about responses from natural microbial communities (using DNA barcoding, multiomics, and functional gene markers) and bioremediation experiments (microcosm and mesocosm) conducted in the presence of petroleum and chemical dispersants in different samples, including soil, sediment, and water. Additionally, we present metabolic mechanisms for aerobic/anaerobic hydrocarbon degradation and alternative pathways, as well as a summary of studies showing functional genes and other mechanisms involved in petroleum biodegradation processes. Graphical abstract: Image 1 Highlights: Microbial communities are diverse in different hydrocarbon-polluted environments. Pseudomonas, Ascomycota and Euryarchaeota were predominant in all sites. Hydrocarbon concentration and chemical dispersant can modulate the microbiome. The structure of microbial communities and metabolisms interfere in oil degradation. Omics approaches help to track functional gene markers (aerobic and anaerobic).